Synergistic effects of long‐wavelength ultraviolet A1 and visible light on pigmentation and erythema. (16th May 2018) - Kohli, I.; Chaowattanapanit, S.; Mohammad, T.F.; Nicholson, C.L.; Fatima, S.; Jacobsen, G.; Kollias, N.; Lim, H.W.; Hamzavi, I.H.
Summary: Ultraviolet (UV) radiations from sunlight that reach the surface of the earth are categorized as UVB (wavelength range 280–320 nm) and UVA (320–400 nm). The UVA is further divided into UVA2 (320–340 nm) and UVA1 (340–400 nm). In the United States and other nations, rules have been set outlining how products that are designed to protect against UVB and UVA should be tested, and there are also strict rules about how these products can be labeled. The SPF (sun protection factor) mainly shows the level of protection against UVB only, and SPF along with "Broad Spectrum" on a label shows protection against both UVB and UVA. The criteria that decide whether or not manufacturers can claim a product gives broad spectrum protection, in the US, primarily focus on protection offered below 370 nm. Visible light (VL), which ranges from 400 nm to 700 nm, is a spectrum of wavelengths that are visible to the human eye. To date, only the UV part of sunlight, which is not visible light, has been considered to cause photodamage (damage caused by sunlight) resulting in skin cancers and photoaging (skin ageing due to the sun). The visible part of the sunlight was considered relatively harmless. This study, from the US, investigated skin responses, in terms of sunburn and tanning, caused by visible light in combination with the tail end of long wavelength UVA1 (referred to as VL+UVA1, 370–700 nm) and compared them to those caused by pure visible light (400–700 nm). The findings of the study show that skin responses, in terms of pigmentation (colouring/tanning) and erythema (redness/sunburn), resulting from VL+UVA1 were stronger than those induced by pure visible light alone. This implies that wavelengths that current broad spectrum sunscreens do not cover can affect pigmentation and erythema. These wavelengths may have a role in conditions aggravated by sun exposure such as melasma and post‐inflammatory hyperpigmentation, especially in patients with skin of color. The development of prodcts that protect against visible light and long wavelength UVA1 will be helpful for these, as well as for the management of certain skin disorders triggered by UVA1 and VL. Abstract : Linked Article:  Kohli et al. Br J Dermatol 2018;178 :1173–1180